As concepções dos professores sobre asa dificuldades no processo ensino-aprendizagem de matemática em duas escolas públicas na cidade de Manaus - Macedo, Derlei Maria Correa de (2013)
The dissertation addresses the teachers' conception of the difficulties in teaching mathematics learning. The research was carried out with 06 teachers in two schools in the city of Manaus. The objective is related to the understanding of the conception of the 6th Grade Elementary School teachers about the difficulties presented in the Mathematics discipline. The data were collected through the application of questionnaires with subjective questions, individual interviews and non-participant observation in the classroom. Qualitative research was chosen and the data analysis focused on Content Analysis from Bardin. Regarding the results found, it was noticed that teachers corroborate with the same conception in relation to the difficulties presented in the discipline of Mathematics by the students. Thus, they were unanimous in stating that the base from the early years and the lack of family support are contributing agents to the deficit students in relation to difficulties in Mathematics. In view of this statement, the our scientific problem has been answered. Mathematics is an Exact Science and, for that, it requires teachers and family to be committed to this process.